Type and incidence of injuries to athletes in the Italian national team competing in the Snowboard World Cup (Report by the Medical commission, Italian Winter Sport Federation) - Tavana, R.; De Girolamo, L.; Panzeri, A.; Banfi, G.; Thiebat, G.; Facchini, F.; Pisoni, C.; Pozzoni, R.; Schoenhuber, H. (Medicina dello Sport, 2011)
Aim. This study analyses the injuries suffered in four consecutive years by the members of the Italian national snowboard team, competing in the three separate disciplines valid for the Olympic Winter Games.